The Influence of the Individual Approach on Student Learning Outcomes in Islamic Education in Junior High School - Safitri, Rika; Hadi, Ihsan; Yanti, Herina; Fatimah, Fatimah; Albizar, Albizar; Kaema, Muhammad Tolal (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2023)
This research aims to describe the application of an individual approach in learning Islamic education and its influence on the learning outcomes of junior high school students. This type of research is quantitative research. It is said to be quantitative research because this research uses the concept of variables. In data collection activities, the measuring tools or instruments used in this research used test techniques. The data processed is in the form of numbers obtained from the results of pretest and posttest students in junior high schools. The results of the research on the influence of the individual approach on student learning outcomes in the subject of Islamic education in junior high schools, namely first, the influence of the individual approach on the learning outcomes of students at state junior high school, the results of the analysis obtained t=6.24 and t table=1.89, then the hypothesis in this study is accepted, so it can be concluded that the learning outcomes pretest higher than the yield pretest before learning the individual approach. Second, the learning outcomes of Islamic education for students who were taught using an individual approach were higher compared to the control class who were taught using conventional methods. The average score of experimental class students was 80.205 while the average score of control class students was 67.27.